Quick-freeze/deep-etch electron microscopy visualization of the mouse posterior pole. (September 2017) - Ismail, Ebraheim N.; Ruberti, Jeffrey W.; Malek, Goldis
Abstract: The mouse is one of the most commonly used mammalian systems to study human diseases. In particular it has been an invaluable tool to model a multitude of ocular pathologies affecting the posterior pole. The aim of this study was to create a comprehensive map of the ultrastructure of the mouse posterior pole using the quick-freeze/deep-etch method (QFDE). QFDE can produce detailed three-dimensional images of tissue structure and macromolecular moieties, without many of the artifacts introduced by structure-altering post-processing methods necessary to perform conventional transmission electron microscopy (cTEM). A total of 18 eyes from aged C57BL6/J mice were enucleated and the posterior poles were processed, either intact or with the retinal pigment epithelium (RPE) cell layer removed, for imaging by either QFDE or cTEM. QFDE images were correlated with cTEM cross-sections and en face images through the outer retina. Nicely preserved outer retinal architecture was observed with both methods, however, QFDE provided excellent high magnification imaging, with greater detail, of the apical, central, and basal planes of the RPE. Furthermore, key landmarks within Bruch's membrane, choriocapillaris, choroid and sclera were characterized and identified. In this study we developed methods for preparing the outer retina of the mouse for evaluation with QFDE and provide a map of the ultrastructure and cellular composition of the outer posterior pole. This technique should be applicable for morphological evaluation of mouse models, in which detailed visualization of subtle ocular structural changes is needed or in cases where post-processing methods introduce unacceptable artifacts. Highlights: A compendium of the morphology of the posterior mouse eye with QFDE is presented. Ultrastructural landmarks of the RPE, Bruch's membrane, choroid and sclera, as visualized with QFDE, are characterized. QFDE provides finer details of the ultrastructure of murine ocular tissue structures compared to cTEM. QFDE is a powerful alternative to traditional post-mortem imaging techniques.